Correlated fast ion stopping in magnetized classical plasma - Nersisyan, H. (ՀՀ ԳԱԱ հրատ.)
The results of a theoretical investigation on the stopping power of ion pair in a magnetized electron plasma are presented, with particular emphasis on the two-ion correlation effects. The analysis is based on the assumptions that the magnetic field is classically strong and that the velocity of the two ions is identical and fixed. Երկմասնիկային զուգակցումների հաշվառմամբ հետազոտված է մագնիսաակտիվ պլազմայում շարժվող իոնային զույգի արգելակման հզորությունը: Ենթադրվում է, որ իոնների արագությունները նույնն են և անփոփոխ, իսկ մագնիսական դաշտը դասականորեն ուժեղ է: С учетом двухчастичных корреляций исследована мощность торможения ионной пары в магнитоактивной плазме. Предполагается, что ионы движутся с одинаковыми постоянными скоростями, а магнитное поле является классически сильным.
Keywords: Physics